Frontal sinus size in South African Later Stone Age Holocene Khoe‐San - (:unkn) unknown (My University, 2024)
Abstract Frontal size variation is comparatively poorly sampled among sub‐Saharan African populations. This study assessed frontal sinus size in a sample of Khoe‐San skeletal remains from South African Later Stone Age contexts. Volumes were determined from CT scans of 102 adult crania; individual sex could be estimated in 82 cases. Sinus volume is not sexually dimorphic in this sample. The lack of frontal sinus aplasia is concordant with the low incidences recorded for other sub‐Saharan African and most other global populations save those that inhabit high latitudes. There is considerable variation in frontal sinus size among global populations, and the Khoe‐San possess among the smallest. The Khoe‐San have rather diminutive sinuses compared to sub‐Saharan Bantu‐speaking populations but resemble a northern African (Sudanese) population. Genetic studies indicate the earliest population divergence within Homo sapiens to have been between the Khoe‐San and all other living groups, and that this likely occurred in Africa during the span of Marine Isotope Stages 8–6. There is scant information on frontal sinus development among Late Quaternary African fossils that are likely either closely related or attributable to Homo sapiens . Among these, the MIS 3 cranium from Hofmeyr, South Africa, exhibits distinct Khoe‐San cranial affinities and despite its large size has a very small frontal sinus. This raises the possibility that the small frontal sinuses of the Holocene South African Khoe‐San might be a feature retained from an earlier MIS 3 population.
Keywords: African Research